Knowledge of things human and divine : Vico's New science and Finnegans wake - Verene, Donald Phillip, 1937- (Yale University Press, 2003)
Maintaining that Joyce is the greatest modern 'interpreter' of Vico, Verene demonstrates how images from Joyce's work offer keys to Vico's philosophy. Verene presents Vico's philosophical thought as it develops in his major works, with Joyce's words and insights serving as a guide.